Bringing History Forward: Learning from Historical Context when Translating Contemporary Health Evidence into Planning Practice. (May 2022) - Paine, Greg; Thompson, Susan; Prior, Jason; Connon, Irena; Kent, Jennifer L.
We describe an historical review of planning documents related to a newly developing high-density locality in Sydney, Australia. The review was undertaken to support the translational component of a larger project investigating how best to include knowledge and experience from the health disciplines to ensure a way of living not hitherto commonplace in Australia is also health-supportive. This article presents (i) key findings from the historical data; (ii) associated learnings about practice, developed to assist the wider translational objectives; and (iii) observations on the potential for such historical reviews to inform better planning practice more broadly.